Gene-edited babies: What went wrong and what could go wrong. - Haoyi Wang; Hui Yang (PLoS Biology, 2019)
During the second World Summit of Human Gene Editing, Jiankui He presented the gene-editing project that led to the birth of two baby girls with man-made C-C chemokine receptor type 5 (CCR5) mutations. This extremely irresponsible behavior violated the ethical consensus of scientists all over the world. His presentation revealed a troubling lack not only of basic medical ethics but also of the requisite understanding of genetics and gene editing. Here, we review the rationale and design of his experiment along with the presented data, and provide our scientific criticism of this misconduct.